2005
DOI: 10.1002/joc.1229
|View full text |Cite
|
Sign up to set email alerts
|

On the episodic nature of derecho-producing convective systems in the United States

Abstract: Convectively generated windstorms occur over broad temporal and spatial scales; however, one of the larger-scale and most intense of these windstorms has been given the name 'derecho'. This study illustrates the tendency for derechoproducing mesoscale convective systems to group together across the United States -forming a derecho series. The derecho series is recognized as any succession of derechos that develop within a similar synoptic environment with no more than 72 h separating individual events. A derec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…In a 15-yr climatological study of derechos (large-scale convectively induced wind storms), Bentley and Sparks (2003) showed that more than half occurred in groups lasting several days. Ashley et al (2005) found similar results when using a larger derecho dataset and more conservative criteria for delineating derecho groupings. Approximately 62% of derechos were members of a series, with most series involving two or three derecho events (ϳ24% of series contained four or more events).…”
Section: Introductionsupporting
confidence: 58%
“…In a 15-yr climatological study of derechos (large-scale convectively induced wind storms), Bentley and Sparks (2003) showed that more than half occurred in groups lasting several days. Ashley et al (2005) found similar results when using a larger derecho dataset and more conservative criteria for delineating derecho groupings. Approximately 62% of derechos were members of a series, with most series involving two or three derecho events (ϳ24% of series contained four or more events).…”
Section: Introductionsupporting
confidence: 58%
“…As a result, very few meteotsunami events have been reported in the Great Lakes to date. Thus, the use of remote sensing observations such as radar radial velocity as well as next‐generation atmospheric and hydrodynamic modeling systems are crucial to improve our ability to understand the mechanisms that cause meteotsunamis and how their frequency and intensity might change with increasingly frequent strong convective events [ Bentley and Sparks , ; Ashley et al ., ]. As enclosed basins, the Great Lakes may pose a unique set of conditions with regard to meteotsunamis, and the ability to detect these extreme storms and predict the hydrodynamic response is crucial to reducing risk and building resilient coastal communities.…”
Section: Discussionmentioning
confidence: 99%
“…affirmed the patterns proposed by these earlier studies in their analysis of derechos. Another interesting finding is the tendency for derechos to group together in families in time and space (Ashley, Mote, & Bentley, 2005;Bentley & Sparks, 2003).…”
Section: Derechosmentioning
confidence: 98%